MIXED MATRIX MEMBRANE ADSORBERS FOR GLYCEROL REMOVAL IN BIODIESEL - Saiful Saiful; Febrina Pratiwi; Ilham Maulana; Muliadi Ramli (Jurnal Natural, 2012)
Mixed matrixmembrane (MMM) adsorbers systems function as short and wide chromatographic columns in which the adsorptive packing consists of one or more micro-porous membranes. This study reports the use of membrane adsorbers for glycerol capturing and removing in crude biodiesel. The MMM are prepared by a wet phase inversion method. Magnesol were incorporated as active sites in the membrane. Matrix support of the membrane was prepared from chitosan.The optimum compositions of the adsorptive membranes were 3 % chitosan, 15% DMF and 60% loading adsorbent. The porosity of these membranes was 34 % and swelling degree was 52 %. The membrane clean water flux was 225 Lm-2h-1 at a trans-membrane pressure of 2.5 bar. The adsorptive membrane has been demonstrated to reduce the concentration of total glycerol in crude biodiesel. The amount of glycerol in biodiesel can be reduced 69.93 % in 60 minute which is agreed to value of SNI quality standards. The membrane adsorber can be regenerated and reused for biodiesel purification. The regenerated membrane can be reused with maintaining the high adsorption capacity. The methanol was better than ethanol to regenerate the magnesol membrane. The Magnesol membrane will be a new alternative method for biodiesel purification.Mixed matrixmembrane (MMM) adsorbers systems function as short and wide chromatographic columns in which the adsorptive packing consists of one or more micro-porous membranes. This study reports the use of membrane adsorbers for glycerol capturing and removing in crude biodiesel. The MMM are prepared by a wet phase inversion method. Magnesol were incorporated as active sites in the membrane. Matrix support of the membrane was prepared from chitosan.The optimum compositions of the adsorptive membranes were 3 % chitosan, 15% DMF and 60% loading adsorbent. The porosity of these membranes was 34 % and swelling degree was 52 %. The membrane clean water flux was 225 Lm-2h-1 at a trans-membrane pressure of 2.5 bar. The adsorptive membrane has been demonstrated to reduce the concentration of total glycerol in crude biodiesel. The amount of glycerol in biodiesel can be reduced 69.93 % in 60 minute which is agreed to value of SNI quality standards. The membrane adsorber can be regenerated and reused for biodiesel purification. The regenerated membrane can be reused with maintaining the high adsorption capacity. The methanol was better than ethanol to regenerate the magnesol membrane. The Magnesol membrane will be a new alternative method for biodiesel purification.